Outpatient‐ or community‐based interventions to prevent SIDS and sleep‐related deaths. Issue 2 (17th December 2019) - Pretorius, Kelly; Rew, Lynn
Abstract: Purpose: To determine the state of science of outpatient‐ or community‐based interventions for sudden infant death syndrome prevention in the United States, an integrative review was completed and studies identified through the application of inclusion and exclusion criteria. Conclusions: Of the nine studies identified, three were randomized controlled trials. There was a wide range of measurement tools and variables measured. The timing of interventions also varied. There was a focus on mothers and African Americans. Lastly, study design and approach have not changed significantly over time. Practice Implications: Findings highlight recommendations for future research: expanding the target population, addressing culture in the development of the intervention or program, including additional providers, such as nurses, in the intervention or program, advancing innovation, and increasing rigor of study design.